(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In this study, the antiradical activity of grape leaves grown in Uzbekistan was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The presence of phenolic compounds, flavonoids, and antioxidants in the chemical composition of grape leaves is one of the main factors determining its effectiveness against free radicals. In the study, an ethanol extract was obtained from grape leaves and its DPPH radical neutralisation activity was measured spectrophotometrically. The results showed that grape leaves have high antiradical activity, which further strengthens the scientific basis for their use in folk medicine.